Early effects of concurrent administration of artesunate-amodiaquine and nifedipine on sperm parameters and sex hormones in guinea pigs: An experimental study - Jonah Sydney Aprioku (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Many antimalarial agents and calcium channel blockers have been demonstrated to alter male reproductive activity. Increasing prevalence of hypertension, therefore, increases concern of male infertility, and concurrent administration of antihypertensive and antimalarial agents in malaria-prone areas. Objective: The study evaluates the reproductive effect of co-administration of artesunate (Ats)-amodiaquine (Amod) and nifedipine (Nif) in male guinea pigs. Materials and Methods: In this experimental study, 24 adult male pigs were divided into four groups (n=6/ each) as one control (given distilled water) and 3 intervention groups (given standard daily dose equivalents of Ats-Amod, Nif or combination of both drugs) for 14 days. Serum levels of testosterone, follicle-stimulating hormone and luteinizing hormone were measured using enzyme-linked immunosorbent assay. Testicular weight was measured and the relative weight (organ-to-body weight ratio) was obtained. Sperm count, motility, and morphology were equally analyzed. Results: Nif treatment produced no significant effect on the hormone levels (p=0.058) and sperm parameters (p=0.0568) that were measured, whereas Ats-Amod and Ats-Amod+Nif decreased testosterone level (p=0.0482), sperm count and motility (p<0.0001), but failed to cause an alteration in follicle-stimulating hormone, luteinizing hormone and sperm morphology. Percentage of motility reduction by Ats-Amod+Nif was greater (p=0.025) compared to Ats-Amod effect. Relative testicular weight was decreased (p=0.046) by Ats-Amod and Ats-Amod+Nif, but unaffected by Nif. Conclusion: The result suggests that short-term administration of standard daily dose equivalent of Nif does not alter hormone levels and sperm indices, while Ats-Amod alone or in combination with Nif decreases testosterone, sperm count, and motility. The combination also results in synergistic inhibition of sperm motility